Pendekatan QFD dalam Merancang Strategi Peningkatan Kualitas Pelayanan Coffeeshop Dirasa Semarang - Saputra, Andika Ricky Edi; Usman, Usman; Farida, Ida; Nuryanto, Imam (Jurnal EMT KITA, 2026)
This study reveals that the service quality at Dirasa Kopi has not fully met customer expectations, as indicated by negative GAP values across all SERVQUAL dimensions. Reliability shows the largest gap, followed by Responsiveness, reflecting a misalignment between promised and delivered services as well as limitations in staff speed and responsiveness. Through Quality Function Deployment (QFD), these findings were translated into improvement priorities, in which staff training was identified as the primary strategy due to its direct influence on service consistency and delivery speed. Expansion of seating areas and additional menu variations serve as supporting measures to enhance customer comfort and overall experience. Thus, the results obtained confirm that improving staff competency is the most determining factor in closing the service quality gap at Dirasa Kopi. The results of this study are expected to serve as managerial guidance for Dirasa Kopi in improving service quality, strengthening service performance, and ultimately enhancing its competitive advantage to remain sustainable and gain customer loyalty.